북동태평양 한국 심해저 연구지역 망간단괴의 지역적 분포와 퇴적환경 - 지상범; 강정극; 오재경; 손승규; 박정기; Chi, Sang-Bum; Kang, Jung-Keuk; Oh, Jae-Kyung; Son, Seung-Kyu; Park, Cheong-Kee (Ocean and polar research, 2003)
Deep-sea bottom photographs acquired in the Clarion-Clipperton fracture zone of the northeast equatorial Pacific were analyzed to reveal the controlling processes for the spatial variation of manganese nodule. The results show that regional-scale occurrence variations of manganese nodule are mainly controlled by primary productivity of surface water, sedimentation rate, and water depth (or carbonate compensation depth). As a result, the diagenetic accretion on nodules increases toward southwest while hydrogenetic accretion increases toward northeast. Considering the northwestward movement of Pacific Plate, this regional-scale variation of manganese nodule occurrence seems to be affected by oceanic environment during the active growth period (Oligocene-Miocene) of Pacific Plate.